Is protracted bacterial bronchitis a new nosological group or an old problem of differential diagnosis of chronic cough in children? - S. I. Ilchenko; A. O. Fialkovska; L. O. Zhukova (Zaporožskij Medicinskij Žurnal)
The purpose is to study the clinical-anamnestic and microbiological features of the protracted bacterial bronchitis (PBB), recurrent bronchitis (RB), chronic bronchitis (CB) in children and to determine the risk factors for the development of chronic bronchitis.